Development of an anti-Salmonella typhi Vi ELISA: assessment of immunocompetence in healthy donors. - Ferry, B; Misbah, SA; Stephens, P; Sherrell, Z; Lythgoe, H; Bateman, E; Banner, C; Jones, J; Groome, N; Chapel, H (2004)
We have developed a solid-phase enzyme-linked immunosorbent assay (ELISA) to study the vaccination responses to Vi capsular polysaccharide of Salmonella typhi (S. typhi Vi) vaccine. Purified S. typhi Vi polysaccharide was biotinylated and bound to streptavidin coated microtitre plates. Reproducibility was determined across a range of IgG antibody levels: mean interassay coefficients of variation (CVs) were <11.9% for non-vaccinated sera with low levels and <11.1% for sera with very high levels of anti-S. typhi Vi IgG. Specificity was assessed by inhibition studies using salmonella antigen. We have developed the ELISA based on normal adult serum responses to test immunization with S. typhi Vi vaccine. We also report here anti-S. typhi Vi IgG levels in a group of healthy preschool children. In non-vaccinated adult sera (n = 104), the median value of anti-S. typhi Vi IgG, expressed in S. typhi Vi arbitrary units (AU/ml), was 5.3 AU/ml and in non-vaccinated sera from children (n = 44) the median value was 1.4 AU/ml. The data from immunization of healthy volunteers (n = 23) show that geometric mean levels of anti-S. typhi Vi IgG were significantly higher (P < 0.0001) for post-vaccination subjects (39.2 AU/ml) compared to paired prevaccination (3.9 AU/ml) values. A total of 21/23 vaccine recipients had <8 AU/ml S. typhi Vi IgG in their sera prior to vaccination and of these 20/21 (95%) exhibited threefold increases and 14/21 (67%) fourfold increases in their S. typhi Vi IgG following vaccination. Based on the data in this study, we propose a threefold increase in anti-S. typhi Vi IgG post-vaccination to be considered a positive vaccination response. The ability to demonstrate clearly an antibody rise in response to immunization with S. typhi Vi capsular polysaccharide vaccine suggests that this is likely to be a useful vaccine for the assessment of B cell function in patients with suspected immune deficiency.